2009
DOI: 10.1002/ppap.200931810
|View full text |Cite
|
Sign up to set email alerts
|

Creating Anti‐Reflective Nanostructures on Polymers by Initial Layer Deposition before Plasma Etching

Abstract: The generation of nanostructures by initial layer deposition and plasma etching offers a simple and cost‐effective method for imparting broadband anti‐reflection properties to polymer optics. In this study, we have investigated the possibility of controlling the structure growth on the cycloolefin polymer Zeonex®. It has been found that the geometry of the emerging nanostructures can be adjusted from “island‐like,” through “sponge‐like,” to “pinholes” merely by changing the thickness of the initial layer befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In this case, the first layer may be designed to be Substance-2 with a high refraction index; the second may be silicon dioxide with a low refraction index for the double-layer anti-reflection coating using the above-mentioned method of the admittance diagram. Moreover, we can pre-deposit a SiOx layer of several nanometers for the anti-reflection coating of the plastic substrate to enhance the adherence of the double layer [16].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the first layer may be designed to be Substance-2 with a high refraction index; the second may be silicon dioxide with a low refraction index for the double-layer anti-reflection coating using the above-mentioned method of the admittance diagram. Moreover, we can pre-deposit a SiOx layer of several nanometers for the anti-reflection coating of the plastic substrate to enhance the adherence of the double layer [16].…”
Section: Resultsmentioning
confidence: 99%
“…The refractive index is 1.82 at 500 nm [19,21]. Variable parameters to obtain different nanostructures on organic materials are: thin seed layers, the ion energy in eV corresponding to the value of bias voltage of ion source APS (Advanced Plasma Source), the oxygen flow and the etching time [22]. In the experiment described here an about 1 nm thick Ta 2 O 5 seed layer was deposited on the melamine layer before etching.…”
Section: Methodsmentioning
confidence: 99%
“…3). Former experiments on etched polymers had shown that a more or less closed silica film on top of ARS is very helpful to provide the system a better environmental and mechanical stability [22]. In the hybrid system, a silica layer was applied as a first step down from the substrate refractive index 1.52 to the silica index 1.46.…”
Section: Properties Of a Nanostructured Silica-melamine-silica Combinmentioning
confidence: 99%
“…In this case, the first layer may be designed using Substance-2 with a high refraction index; and the second may be silicon dioxide with a low refraction index for the double-layer anti-reflection coating, using the above-mentioned method of the admittance diagram. Moreover, we can pre-deposit a SiO x layer of several nanometers for the anti-reflection coating of the plastic substrate to enhance the adherence of the double layer [18].…”
Section: Sample T (Mw) T (%) R (μW)mentioning
confidence: 99%